A liquefaction incident in a fill raise: A case study - F. Hassani; J. Ouellet; P. Gauthier; K. Moozar (Canadian Institute of Mining, Metallurgy and Petroleum, 2004)
"This paper describes a sudden spill of waste rock used for backfilling from a waste pass at an underground mine in Canada, thus causing a major failure/accident. The mine operator immediately launched a detailed investigation to understand the causes of this accident and develop procedures to prevent any recurrence of such events in the future. The authors from McGill University were invited to collaborate with the engineers at the mine to examine this accident. The events leading to the accident were studied, appropriate measurements were taken and samples of the waste material were collected for further testing and analysis.The field visit and the interview of the witnesses allowed the detailed documentation of the events. The sequence of events related to the incident, along with the experimental results obtained in the course of the investigation, are presented. The waste material was characterized in the laboratory with regard to its behaviour in the presence of water. This information is discussed and the failure mechanism involved in the accident is identified. Finally, the full recommendations as well as the immediate operational measures implemented by the mine to prevent the future occurrence of such events are presented and discussed."